Pengaruh Harga, Produk Dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan (Studi Pengunjung Cafe Cuci Mulut Depok - Rizki Nurul Nugraha; Raden Ajeng Dhea Ayu Salsabila (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to examine and analyze the effect of Price, Product and Service Quality on Customer Satisfaction Caffe Washing Mouth Depok. In this study, the data collection method used a survey method with the instrument of distributing questionnaires as many as 100 samples to 100 customers who visited the Caffe Washing Mouth Depok. Analysis of the data in this study using the help of SPSS. The testing techniques of this study include the Validity Test, Reliability Test, Classical Assumption Test, and Multiple Linear Analysis Test. The results showed that price, product and service quality had a positive and significant effect on customer satisfaction by using quantitative research methods.